In vivo antimicrobial activity of 0.6% povidone-iodine eye drops in patients undergoing intravitreal injections: a prospective study - Daniele Tognetto (Nature Portfolio, 2021)
Abstract To investigate the antimicrobial activity of a preservative-free 0.6% povidone-iodine eye drop as an antiseptic procedure in decreasing the conjunctival bacterial load in eyes scheduled for intravitreal treatment and to compare its efficacy to the untreated fellow eye used as the control group. Prospective cohort analysis in which 208 patients received preservative-free 0.6% povidone-iodine eye drops three times a day for three days before intravitreal injection. Before and after the prophylactic treatment, a conjunctival swab was collected from both the study eye and the untreated contralateral eye, used as control. The swab was inoculated on different culture media and the colony-forming units were counted. Bacteria and fungi were identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry. Treatment with 0.6% povidone-iodine eye drops significantly reduced the conjunctival bacterial load from baseline (p < 0.001 for blood agar and p < 0.001 for chocolate agar) with an eradication rate of 80%. The most commonly isolated pathogen at each time-point and in both groups was coagulase-negative Staphylococci, isolated in 84% of the positive cultures. The study provides evidence about the effectiveness of 0.6% povidone-iodine eye drops treatment in reducing the conjunctival bacterial load in eyes scheduled for intravitreal treatment.